2018
DOI: 10.3390/w10050641
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Health-Risk Assessment of Trace Metals in Raw and Boiled Drinking Water from Rural Areas of China

Abstract: Abstract:In order to assess the exposure of rural residents to trace metals via drinking water ingestion, 222 drinking water samples of rural areas from 8 provinces in China were collected and 18 trace metals analyzed by inductively coupled plasma mass spectrometer (ICP-QMS). Based on metal concentrations, the health-risk assessment such as chronic daily intakes (CDI) and hazard quotient (HQ) were calculated. Results showed that most metals occurred in the drinking water at very low concentrations, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
(72 reference statements)
2
15
1
Order By: Relevance
“…In addition, high Zn levels in tap water (Table 1) were found to be over 100 times higher than those shown by a related study in Central Uganda [10], probably due to weaker water quality practices in rural communities of Uganda. In China, high Zn levels in drinking water have been associated with mining activities [47]; however, there was no evidence for this in Bushenyi district of Southwestern Uganda where these samples were collected showing that environmental contamination with Zn was related to the heavy pesticide usage which is common in many agricultural ecosystems [16, 48]. Furthermore, Cu concentrations were highest in tap water (Table 1) possibly due to the use of copper pipes in the transportation of water by the Uganda National Water and Sewerage Cooperation (UNWSC).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high Zn levels in tap water (Table 1) were found to be over 100 times higher than those shown by a related study in Central Uganda [10], probably due to weaker water quality practices in rural communities of Uganda. In China, high Zn levels in drinking water have been associated with mining activities [47]; however, there was no evidence for this in Bushenyi district of Southwestern Uganda where these samples were collected showing that environmental contamination with Zn was related to the heavy pesticide usage which is common in many agricultural ecosystems [16, 48]. Furthermore, Cu concentrations were highest in tap water (Table 1) possibly due to the use of copper pipes in the transportation of water by the Uganda National Water and Sewerage Cooperation (UNWSC).…”
Section: Discussionmentioning
confidence: 99%
“…It describes the degree of harm to the human body under various exposure pathways, and proposes recommendations to protect human health [19][20][21][22][23][24][25][26]. HHRA is based on four steps; hazard identification, dose-response assessment, exposure assessment, and risk characterization [27][28][29][30][31][32][33][34][35].…”
Section: Human Health Risk Assessment Model and Parameter Acquisitionmentioning
confidence: 99%
“…The attribution of these incidents and factors influencing their frequency, severity, and consequences has been the subject of many investigations [6][7][8][9]. Of these incidents, contamination in the distribution network, including household plumbing, proves to be the most challenging to detect and control [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, sampling done at "supply points to consumers" usually means that the samples are taken before they enter the household. Several studies have reported increased concentrations of contaminants in the household tap due to factors related to plumbing, water temperature, and stagnation [13,15,16].…”
Section: Introductionmentioning
confidence: 99%